Marketing Strategy of Akad Murabahah Bil Wakalah Financing Products to Increase Customer Interest at Bank Muamalat KC Denpasar - Heriyadi Heriyadi; R Agrosamdhyo; Iswahyuni Iswahyuni (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
This study focuses on the marketing strategy of the Murabahah bil Wakalah financing product at Bank Muamalat Indonesia KCU Denpasar, Badung Regency, Bali. Murabahah is a sales contract that states the acquisition price and the agreed profit margin, while wakalah is the delegation of purchasing goods on behalf of the first party. The study aims to examine the marketing strategy and customer interest in this financing product. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and triangulation, and data analysis techniques including data reduction, data presentation, and conclusion drawing. The results show that the marketing strategy includes several elements: product (iB Hijrah Multiguna Consumer Financing and iB Muamalat KPR), price (transparent and mutually agreed upon), place (strategic office location), promotion (social media, website, email marketing), people (professional staff), process (focused on customer satisfaction), and physical evidence (supportive physical elements). Customer interest is influenced by internal factors, trust, and a sense of security. The study's implications can serve as a reference for Bank Muamalat to increase the attractiveness of financing products to customers.